A new interstitial species of the Hydroporus ferrugineus group from north-western Turkey, with a molecular phylogeny of the H. memnoniusand related groups (Coleoptera: Dytiscidae: Hydroporinae) - Hernando, Carles; Aguilera, Pedro; Castro, Agustín; Ribera, Ignacio (Zootaxa, 2012)
We describe Hydroporus bithynicus sp. n. (Coleoptera, Dytiscidae, Hydroporinae) from the Bolu province in north-west-ern Turkey. The species belongs to the newly defined H. ferrugineus group, and can be separated from the other two mem-bers (H. ferrugineus Stephens, 1829 and H. sanfilippoi Ghidini, 1958) by its more flattened shape, less developed eyesand shape of male genitalia. Its external morphology and the habitat in which all specimens were found (a small pool withupwelling spring water next to a stream) suggest an interstitial habitat, similar to that reported for other species of thegroup. We present a molecular phylogeny of the species of the H. memnonius and H. longulus groups, including somerepresentatives of the main lineages within the genus, based on ca. 2 kb of four mitochondrial genes. We redefine the H.memnonius group and recognise the H. ferrugineus, H. obsoletus and H. morio groups of species as separate entities. Hy-droporus neglectus Schaum, 1845 was found to be related to the species of the H. angustatus, but not the H. memnonius group.